NMR Investigation of Protein‐Carbohydrate Interactions: The Recognition of Glycans by Galectins Engineered with Fluorotryptophan Residues. Issue 5 (12th December 2022) - Lete, Marta G.; Franconetti, Antonio; Bertuzzi, Sara; Delgado, Sandra; Azkargorta, Mikel; Elortza, Félix; Millet, Oscar; Jiménez‐Osés, Gonzalo; Arda, Ana; Jiménez‐Barbero, Jesús
Abstract: Fluorine ( 19 F) incorporation into glycan‐binding proteins (lectins) has been achieved and exploited to monitor the binding to carbohydrate ligands by nuclear magnetic resonance (NMR) spectroscopy. Galectins are a family of lectins that bind carbohydrates, generally with weak affinities, through a combination of intermolecular interactions including a key CH‐π stacking involving a conserved tryptophan residue. Herein, Galectin‐3 (Gal3) and Galectin‐8 (Gal8) with one and two carbohydrate recognition domains (CRDs), respectively, were selected. Gal3 contains one Trp, whereas Gal8 contains three, one at each binding site and a third one not involved in sugar binding; these were substituted by the corresponding F‐Trp analogues. The presence of fluorine did not significantly modify the affinity for glycan binding, which was in slow exchange on the 19 F NMR chemical‐shift timescale, even for weak ligands, and allowed binding events taking place at two different binding sites within the same lectin to be individualized. Abstract : The incorporation of single‐ 19 F‐tryptophan residues into two glycan binding proteins, Galectin‐3 and Galectin‐8, was exploited to monitor their binding to carbohydrate ligands by using NMR spectroscopy. Although the affinity of the molecular recognition events was not substantially altered, 19 F NMR spectroscopy provided interesting added values with respect to other NMR binding strategies.